Anti-CD47 treatment enhances anti-tumor T-cell immunity and improves immunosuppressive environment in head and neck squamous cell carcinoma. (3rd April 2018) - Wu, Lei; Yu, Guang-Tao; Deng, Wei-Wei; Mao, Liang; Yang, Lei-Lei; Ma, Si-Rui; Bu, Lin-Lin; Kulkarni, Ashok B.; Zhang, Wen-Feng; Zhang, Lu; Sun, Zhi-Jun
ABSTRACT: Head and neck squamous cell carcinoma (HNSCC) is considered as an immunosuppressive disease, with impaired tumor-infiltrating T lymphocytes and increased suppressive immune cells. The efficacy of CD47 antibodies in immune checkpoint therapy is not clearly understood in HNSCC. In this study, human tissue microarrays and immunocompetent transgenic mouse models were used to explore the expression of CD47 and the use of CD47 antibodies in HNSCC. We identified overexpression of CD47 in HNSCC as compared with the control normal human tissue and also in HNSCC mouse models. The expression of CD47 also correlated with clinicopathological parameters as well as outcome. Furthermore, inhibition of CD47 delayed tumor growth and improved tumor microenvironment by stimulating effector T cells and decreasing suppressive immune cells and regulating the function of CD11b + Ly6G + MDSC. Our data suggest that CD47 blockade may be a potential immunotherapeutic target in human HNSCC.